THE PECULIARITIES OF GROWTH, DEVELOPMENT AND CULTIVATION OF PRINSEPIA SINENSIS (OLIV.) KOM. UNDER THE CONDITIONS OF THE REPUBLIC OF MOLDOVA - Ion Roșca; Elisaveta Onica; Alina Cutcovschi-Muștuc; Vitalie Mîțu (Agricultura, 2022)
The bioecological peculiarities of growth, development and cultivation of Prinsepia sinensis (Oliv.) Kom. have been studied and described. This shrub multiplies generatively and vegetatively – by lignified cuttings and by division. The optimal and most cost-effective method of multiplication was sowing fresh seeds, in early autumn, at a depth of 2-3 cm. The germination capacity of the seeds sown in autumn varied in the research years and was on average 60-70%, and of those sown in spring after stratification – only 40-50% depending on the weather conditions and the techniques applied during the growing season. The researched species is appreciated for its ornamental qualities, particularly in early spring, when it produces numerous bright yellow flowers of unique beauty, and in early autumn – with hanging branches full of dark red fruits.